2020
DOI: 10.3390/cancers12113165
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Extracellular Vesicles: Next-Generation Diagnostic and Drug Delivery Nanotools

Abstract: Nanosized extracellular vesicles (EVs) with dimensions ranging from 100 to 1000 nm are continuously secreted from different cells in their extracellular environment. They are able to encapsulate and transfer various biomolecules, such as nucleic acids, proteins, and lipids, that play an essential role in cell‒cell communication, reflecting a novel method of extracellular cross-talk. Since EVs are present in large amounts in most bodily fluids, challengeable hypotheses are analyzed to unlock their potential rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 270 publications
(294 reference statements)
1
16
0
Order By: Relevance
“…Compared to other drug carriers, such as lipidosomes and viruses, EVs induce a lesser immune response, and their drug transfer efficiency is also excellent. 71 They have been used to deliver nucleic acids, proteins and small molecule drugs to targeted cells or tissues in oncotherapy. 15 , 72 , 73 For example, one study showed that EVs derived from patient body fluids can be modified by electroporation to carry exogenous siRNA and then transport the siRNA to human blood cells (monocytes and lymphocytes).…”
Section: The Application Of Tevs In Tumor Immunotherapymentioning
confidence: 99%
“…Compared to other drug carriers, such as lipidosomes and viruses, EVs induce a lesser immune response, and their drug transfer efficiency is also excellent. 71 They have been used to deliver nucleic acids, proteins and small molecule drugs to targeted cells or tissues in oncotherapy. 15 , 72 , 73 For example, one study showed that EVs derived from patient body fluids can be modified by electroporation to carry exogenous siRNA and then transport the siRNA to human blood cells (monocytes and lymphocytes).…”
Section: The Application Of Tevs In Tumor Immunotherapymentioning
confidence: 99%
“…In an effort to reduce these toxic side effects and enhance the clinical utility of DOX, many have sought to develop nano-scale drug-delivery systems [ 12 ], with lipid-based particles being the most common particle type owing to their perceived safety. Nanomedicines offer a number of advantages over traditional drug-delivery strategies, including excellent bioavailability, prolonged stability while in circulation, improved drug solubility, an ability to shield off-target tissues from the effects of the encapsulated drugs [ 13 , 14 , 15 , 16 ], and a lower risk of opsonization [ 17 , 18 ]. The enhanced permeability and retention effect (EPR) enables the preferential accumulation of nanoparticles within tumor tissues [ 19 ] owing to the relatively poor lymphatic drainage and dysregulated endothelial vasculature within these malignancies [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although several methods such as ultracentrifugation, density gradient centrifugation, chromatography, filtration, polymer-based precipitation, and immunoaffinity have been adopted to isolate pure exosomes without contamination, there is still a lack of consistency and agreement. 105 Isolation of exosomes along with non-exosomal materials and damaged exosomal membranes creates artifacts and alters the protein and RNA profiles. Since exosomes are obtained from a variety of sources, the composition of proteins/lipids influences the sedimentation properties and isolation.…”
Section: Factors Controlling the Biogenesis Of Exosomesmentioning
confidence: 99%